Brassinosteroid control of shoot gravitropism interacts with ethylene and depends on auxin signaling components1. Issue 1 (1st January 2013) - Vandenbussche, Filip; Callebert, Pieter; Zadnikova, Petra; Benkova, Eva; Van Der Straeten, Dominique
Abstract : Premise of the study: To reach favorable conditions for photosynthesis, seedlings grow upward when deprived of light upon underground germination. To direct their growth, they use their negative gravitropic capacity. Negative gravitropism is under tight control of multiple hormones. Methods: By counting the number of standing plants in a population or by real time monitoring of the reorientation of gravistimulated seedlings of Arabidopsis thaliana, we evaluated the negative gravitropism of ethylene or brassinosteroid (BR) treated plants. Meta‐analysis of transcriptomic data on AUX / IAA genes was gathered, and subsequent mutant analysis was performed. Key results: Ethylene and BR have opposite effects in regulating shoot gravitropism. Lack of BR enhances gravitropic reorientation in 2‐d‐old seedlings, whereas ethylene does not. Lack of ethylene signaling results in enhanced BR sensitivity. Ethylene and BRs regulate overlapping sets of AUX / IAA genes. BRs regulate a wider range of auxin signaling components than ethylene. Conclusions: Upward growth in seedlings depends strongly on the internal hormonal balance. Endogenous ethylene stimulates, whereas BRs reduce negative gravitropism in a manner that depends on the function of different, yet overlapping sets of auxin signaling components.